2017
DOI: 10.17341/gazimmfd.300608
|View full text |Cite
|
Sign up to set email alerts
|

AA 5754-O ALAŞIMININ ILIK DERİN ÇEKİLMESİ ÜZERİNE KALIP YÜZEY AÇISI ve BASKI PLAKASI KUVVETİNİN ETKİSİNİN DENEYSEL ARAŞTIRILMASI

Abstract:  AA5754-O alaşımının ılık derin çekilmesi  Et kalınlığı ve şekillendirme kuvvetine sıcaklık, kalıp yüzey açısı ve baskı plakası kuvvetinin etkisi  Çekilen kaplardaki sertlik ve geri yaylanma ilişkisi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
1
2
0
1
Order By: Relevance
“…Within the scope of the study, it is observed that when the temperature is increased from room temperature to 250 °C, the forming force decreases by an average of 20.55% (table 2). This situation is consistent with the literature [4] that analysed the effect of different temperatures on the stamping force of AA5754 sheet material in deep drawing processes using experimental and finite element methods. According to the analysis results, when the temperature was increased from room temperature to 250 °C, the stamping force decreased by approximately 22.69%.…”
Section: Analyses Of Warm Deep Drawing Process Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Within the scope of the study, it is observed that when the temperature is increased from room temperature to 250 °C, the forming force decreases by an average of 20.55% (table 2). This situation is consistent with the literature [4] that analysed the effect of different temperatures on the stamping force of AA5754 sheet material in deep drawing processes using experimental and finite element methods. According to the analysis results, when the temperature was increased from room temperature to 250 °C, the stamping force decreased by approximately 22.69%.…”
Section: Analyses Of Warm Deep Drawing Process Resultssupporting
confidence: 92%
“…An important advantage of this process is that it is carried out below the recrystallization temperature, the microstructure does not change, and the sheet material's mechanical properties are unaffected. Developing warm-forming processes in the automotive and aerospace industries is crucial to produce lighter vehicles using aluminium and magnesium alloys to reduce fuel consumption and lower exhaust emissions [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Özek ve Taşdemir'in bir başka çalışmasında ise AA 5754-O alaşımının oda sıcaklığı, 100°C, 175°C ve 250°C sıcaklıklarda kalıp ve baskı plakası yüzeylerine 0°, 5°, 10° ve 15°'lik açılar vererek derin çekmeye olan etkilerini araştırmışlardır. Araştırma sonucunda, sıcaklığın etkisiyle baskı plakası kuvvetindeki artışa rağmen et kalınlığı değişiminin azaldığını, sıcaklık ve kalıp yüzey açısı ile birlikte malzeme akışının kolaylaştığını, kalınlık dağılışının daha homojen hale geldiğini ve sıcaklığın artmasıyla geri esnemenin azaldığını belirlemişlerdir [13].…”
Section: = Dunclassified
“…Although the lubrication conditions, microstructure and temperature plays a dominant role during a deep drawing process, geometrical features of the die setup such as die shoulder radius, punch edge radius and die angle have deterministic effects on the deep drawing process [21]- [24]. In literature, it has been stated that the use of a conical die for the deep drawing process may enhance the DDR [25], [26].…”
Section: Introductionmentioning
confidence: 99%